Urbanization with Chinese characteristics the Hukou system and migration - Chan, Kam Wing; Cai, Fang 1956-; Wan, Guanghua 1961-; Wang, Man (Routledge, Taylor & Francis Group, 2018)
Building on his three decades of careful research, Professor Kam Wing Chan expertly dissects the complexity of China's hukou system, migration, urbanization and their interrelationships in this set of journal articles published in the last ten years. This book examines several fundamental issues in China's migration and urbanization: the definitions of and statistics about cities and migration, the hukou system, the rural migrant workers, and the government's 2014 new-type urbanization blueprint
Includes bibliographical references and index
Keywords: Registrierung; Wohnsitz; Verstädterung; Stadtviertel; Migration; China